Sistema de información del Muyuna Amazon Lodge para el incremento de sus ventas, satisfacción de los turistas visitantes y contribución a la educación de la comunidad de San Juan de Yanayacu al 2023 - Fernandez Macedo, Cristina (2025)
The thesis titled MUYUNA AMAZON LODGE INFORMATION SYSTEM TO INCREASE ITS SALES, SATISFACTION OF VISITING TOURISTS AND CONTRIBUTION TO THE EDUCATION OF THE COMMUNITY OF SAN JUAN DE YANAYACU BY 2023 developed by the graduate in International Business and Tourism, CRISTINA FERNANDEZ MACEDO, through the non experimental quantitative descriptive design that analyzes the indicators that the variables of his hypothesis have, has reached the following conclusions. It has been determined that the PPE system used by the guides of the company Muyuna Amazon Lodge is adequate due to the fact that 76% of visitors who have used it consider it good. An increase in sales has been demonstrated between the year 2019 compared to 2024 by an average of $550.00 dollars and in the year 2023 there has been an average increase of $14,410.00 dollars. The level of satisfaction with the food received from 22 visitors in the sample represents 88% and is considered HIGH. Likewise, the punctuality of the operations expressed by 21 visitors represents 84%, expressing a HIGH level. The contribution to the development of education in the Yanayacu community is manifested with additional support to the community's educational system developed by the Ministry of Education, in which a large participation is recorded.